Implementasi Program Pengajaran Agama Dalam Membangun Karakter Islami Di Majelis Taklim Syuhada Medan Sunggal - T Aldi Rizki Pratama; Manshuruddin Manshuruddin; Abdi Syahrial Harahap (Journal Of Dehasen Educational Review, 2026)
This study aims to describe the implementation of a religious education program to build Islamic character at the Syuhada Medan Sunggal Islamic Boarding School (Majelis Taklim Syuhada Medan Sunggal). The method used was descriptive qualitative, with data collection techniques of observation, in-depth interviews, and documentation studies. The research subjects included the Community Empowerment Agency (BKM), religious teachers, and members of the congregation, selected purposively. The results indicate that the implementation of the religious education program to build Islamic character is carried out in an integrated manner with positive religious activities. Character values such as discipline, responsibility, social concern, and noble morals are instilled in the daily lives of the congregation. Activities such as congregational prayer, Qur'an recitation, and Islamic jurisprudence (fiqh) studies are effective media in building character. The conclusion of this study is that the Majelis Taklim is able to create a non-formal educational environment conducive to strengthening the character of the congregation as a whole.